Original paperSAPHO syndrome – heterogeneity of clinical course – diagnostic problems - Zielińska, Agnieszka; Rupiński, Robert; Filipowicz-Sosnowska, Anna (Reumatologia/Rheumatology, 2006)
SAPHO syndrome is a heterogeneous disorder that involves bone, joints with multifocal location, skin and organs. The most frequent forms of bone and joint involvement are: anterior wall pain, spine pain and swelling of sterno-clavicular joints. The most frequent forms of skin involvement are palmo-plantar pustulosis and acne, although a lack of skin involvement does not preclude disease diagnosis. The disease course varies between patients from mild forms to severe. The article presents differences in clinical manifestation and disease course in 9 observed patients. Laboratory and radiological results and therapeutic possibilities are discussed.